Studies of the design layout of resistojet with porous structure for propulsion systems of small spacecraft - V. N. Blinov; V. V. Kositsin; A. I. Lukyanchik (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The results of experimental studies on nitrogen with an overpressure of 0,02 MPa resistojet propulsion system of a small spacecraft with a porous structure weighing 45 g and an autonomous heating element with a radius of 3 mm with a power consumption of up to 60 watts for a warm-up time of up to 300 s are presented. The possibility of using a porous structure as a volumetric fuel gas pipeline with an increase in heat transfer intensity has been experimentally proved and the actual specific heat capacity of the porous structure has been determined. Taking into account the actual specific heat capacity, theoretical studies of the mass and geometry of the porous structure in the resistojet composition are carried out, optimal with respect to the autonomous heating element used by the power and the amount of fuel heating in the range (573–1273) K. Taking into account the radius of the heating element, the fuel temperature range (573–973) K corresponding to the optimal masses and radii of the porous structure for the formation of the resistojet design layout is determined.